2021
DOI: 10.1186/s12939-020-01352-8
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic variations in risky sexual behavior among adolescents in 14 sub-Saharan Africa countries who report ever having had sex

Abstract: Background Equity is a guiding principle of the Global Strategy for Women, Children and Adolescents’ Health (2016–2030) aimed at improving adolescent health and responding more effectively to adolescents’ needs. We investigated the socioeconomic differentials in having multiple sexual partners and condom use among unmarried adolescents who reported ever having had sex aged 15–19 years in 14 sub-Saharan countries. Methods Using the most recent publi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
12
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 33 publications
9
12
0
2
Order By: Relevance
“…Our results allow the comparison of inequalities across various HIV-related indicators. Overall, we did not observe large socioeconomic disparities in reporting having multiple sexual partners, consistently with recent results [27]. Large absolute and relative inequalities, overall, remain regarding lack of knowledge and stigmatizing attitudes toward PLHIV, and this may undermine HIV prevention, care and treatment [28].…”
Section: Discussionsupporting
confidence: 88%
“…Our results allow the comparison of inequalities across various HIV-related indicators. Overall, we did not observe large socioeconomic disparities in reporting having multiple sexual partners, consistently with recent results [27]. Large absolute and relative inequalities, overall, remain regarding lack of knowledge and stigmatizing attitudes toward PLHIV, and this may undermine HIV prevention, care and treatment [28].…”
Section: Discussionsupporting
confidence: 88%
“…In addition, close to half (48.7%) did not use a condom in their last sex, higher prevalence seen among Sierra Leoneans (58.6%) than Liberians (39.8%), and our ndings for both countries higher than the prevalence reported in studies conducted in Mozambique, Ghana and Ethiopia [11,31,34]. Our study's high prevalence of risky sexual behaviour is consistent with previous community-based studies conducted among adolescents and youths in both countries [7][8][9]29] and similar studies in other African countries [1,4,11,31]. The higher prevalence of risky sexual behaviour in our study may be attributed to increased trauma and economic hardships, changes in parenting styles, breakdown in the social fabric in our society and broken homes experienced by young people, which is due to civil war and lately the Ebola outbreak in these two countries [37][38][39].…”
Section: Resultssupporting
confidence: 88%
“…Another study among Liberian youths found that 34% of those who were sexually active did so before the age of 15 (early sexual debut), and 21% of those who were sexually active had several sexual partners, and 26% of sexually active teenagers had never used a condom, 11% had gotten pregnant or helped someone become pregnant one or more times, and 11% had been sexually assaulted [8].A recent study reported that majority of sexually active Sierra Leone youths had condomless sex in their last sexual encounter [9]. A United Nations Population Fund report on the impact of Ebola on adolescent pregnancy in Sierra Leone found that close to half had their rst pregnancy during the Ebola outbreak period and close to a third had used ever use of any kind of family planning [10].…”
Section: Introductionmentioning
confidence: 99%
“…The finding of this study indicates that lower education attainment among adolescents who experienced SRB compared with those who had not experienced SRB is corroborated by findings from other adolescent health studies within the Kenyan context (89,90). It is also reported that while most young adolescents (i.e., those who are 0-14 years old) have not initiated sexual intercourse, some are already exploring intimate relationships without adequate information to make informed decisions about their sexual and reproductive health (91).…”
Section: Discussionsupporting
confidence: 87%